Peran Botoh dalam Pemilihan Kepala Desa: Studi Konflik Politik Kepala Desa Sotabar, Kecamatan Pasean, Kabupaten Pamekasan - M. Fahri Ilham Akbar; Aribowo Aribowo (Universitas Airlangga, 2022)
Botoh (voice brokers) in the areas of Central Java and East Java have an important role in winning the candidates carried out in the lowest level general elections (pilkades). Solid strategies in the selection of candidates are not responsible for the method of funding, surveying, and control of dominance held in the image of society. General Election of Village Heads in Sotabar Village, Pasean Subdistrict, Pamengkasan Regency is an arena for strong power shows in winning the candidates they carry. Many conflicts occur in the pilkades because of differences of opinion, struggles for power and interests. Between the election of village heads (pilkades) and the political dynamics between botoh, petahanats and the community. The findings of the data show that Botoh has an important role associated with the search for candidates to win. In addition, botoh is a person who has the legitimacy of power in society, the experience of freedom in the world of photography and high relations with political officials. When political practices were implemented, Botoh implemented mobilization by reading the conditions of the community and carried out carefully in the three groups approved by the clerics, santri and abangan through the team provided. Even in the winning process, it is through some political dynamics with other actors that cause conflict. This conflict is triggered by the relationship between slaughterhouse and petahanat related to unbalanced authority and leadership that is not in line with the expectations of the community.